Strategies to shift adolescents out of cars: a qualitative study among adolescents and parents - Venurs Loh; Shannon Sahlqvist; Jenny Veitch; Chahana Paudel; Anna Timperio (BMC Public Health)
Abstract Background Promoting active travel is a promising and sustainable strategy to mitigate declining physical activity among adolescents. However, interventions to increase active travel among this age group is rare. This study aimed to explore strategies adolescents and parents consider most effective for adolescents to replace short car trips with active travel. Methods Adolescents (n = 22; mean age of 16 ± 0.9 years; 45% girls) and parents of adolescents (n = 20; mean age of their adolescents = 14.6 ± 1.9 years; 45% girls) living in Melbourne or Geelong, Australia were recruited from social media platforms and convenience sampling. One-on-one online interviews via Zoom were conducted. Participants were asked about strategies that would encourage them (their adolescent) to switch from car travel to walking and cycling. The interviews were audio-recorded, transcribed verbatim, and analyzed using qualitative content analysis in NVivo 14 software (QSR International PTY Ltd, Melbourne, Australia). Results Key themes that emerged from the data were similar for both adolescents and parents of adolescents. These were: (1) provide access to or improve walking and cycling infrastructure, (2) develop capability, (3) incentive-based interventions, (4) improve car driver behavior, (5) discourage car parking, and (6) shift social norms. Conclusion To encourage uptake of active travel and discourage car dependency for short distance trips among adolescents, a multisectoral approach intervening at multiple levels is important to support behavior change towards more active and sustainable transportation. Findings from this study can support the development of youth-centered interventions to promote physical activity and sustainable transport.